Evaluasi Tingkat Keselarasan Strategi Bisnis dan Strategi Teknologi Informasi Studi Kasus PT.Indosat Tbk - , Tri Indah Prihatini, Ahmad Jamli, Drs, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Even after a decade of research and discussion, strategic alignment between IT (Information Technology) and business strategy, remains an enduring challenge for firms worldwide, like PT.Indosat Tbk. In this study, the authors found that the degree of alignment of IT strategy and business strategy in Indosat is still relatively poor. And as we all know that the telecommunications industry such as Indosat has two important pillars that determine the success of the company, that is the role of IT and business. Alignment between IT strategy and business strategy is one thing that is the duty of a CEO and it is one of the factors that support the implementation of good strategic management in a company. On this occasion, we will discuss the degree of alignment between IT and business strategy in Indosat, what are the gaps in achieving the alignment and how the strategy alignment gaps could be minimized. This research mostly will use the questionnaire method and some data will be gathered through interview techniques. The material and content of the questionnaire would be more use of the Capability Maturity Model developed by Carneggie Mellon's Software Engineering and also from Norton et al. It can be seen that the degree of alignment between IT and business strategy in Indosat is still relatively low. Therefore, the author will seek and find solutions that could be minimized the strategy alignment gaps. Indosat as one of the largest telecommunication provider in Indonesia still faces a classic and quite fundamental problems, ie the degree of alignment between IT and business are still low. There are many gaps that are found in order to achieve alignment between IT and business. The alignment later will become the main subject of this research further.